Historical trauma: the impact of colonial racism on contemporary relations between African Americans and Mexican immigrants - Wright, Noah M., author; Ishiwata, Eric, advisor; Cespedes, Karina, committee member; Breaux, Richard, committee member; Taylor, Peter, committee member (Colorado State University. Libraries, 2011)
The purpose of this project is to examine tensions in present day United States between African Americans and Mexican immigrants. Hyper-violent incidents of interracial gang violence between these two communities are presented by mainstream media as signifiers of the existence of the tension. Latinos, as a whole, and African Americans, whether in gangs or civilians, are often portrayed to be in competition due to three conventional explanations. While scholars and media sources have validity in pointing out the significance of socioeconomic competition, struggles for political power and the problems that the language barrier create, these explanations are not complete. El sistema de castas or the caste system, a racial hierarchy created by the Spaniards in Latin America during their colonial efforts, established how people of African descent, both free and slave, were treated in New Spain. The caste system's continued influence can be seen with the denial of African heritage and the marginalized position of Afro-Mexicans in present day Mexico. Furthermore, these prejudices remain intact when Mexican immigrants enter the U.S. It is understood that Mexico's national identity is mestizaje, a racially mixed nation; however, racism existed and is also present today in Mexico. By combining a historical perspective with the three primary reasons, mentioned above, it is hoped that the complete picture will help resolve tensions. This thesis argues that colonization, influenced heavily by a racial hierarchy, has caused Mexican immigrants to carry with them prejudices towards African Americans that were learned in Mexico, showing that the issue is deeper than competition over resources in present times. In response to an influx of Latino immigrants, African American responses show parallels with historical nativist responses to immigrants. By combining the impacts of historical racism with conventional explanations for the existence of the tension it is hoped an understanding may develop that will help reduce conflict.
Keywords: caste system; interracial gangs; Denver